Let's solve each equation step-by-step to determine whose statements are correct.
Equation A: \[ 3(4 - 5h) - 7 = -12 + 2h \]
Expanding: \[ 12 - 15h - 7 = -12 + 2h \] \[ 5 - 15h = -12 + 2h \]
Rearranging gives: \[ 5 + 12 = 15h + 2h \] \[ 17 = 17h \] \[ h = 1 \]
Equation B: \[ 2(p - 3) - 1 = 6p + 142 \]
Expanding: \[ 2p - 6 - 1 = 6p + 142 \] \[ 2p - 7 = 6p + 142 \]
Rearranging gives: \[ -7 - 142 = 6p - 2p \] \[ -149 = 4p \] \[ p = -\frac{149}{4} \]
Equation C: \[ 23v - 3 + 83 = -1 \]
Combining terms: \[ 23v + 80 = -1 \]
Rearranging gives: \[ 23v = -1 - 80 \] \[ 23v = -81 \] \[ v = -\frac{81}{23} \]
Summary of solutions:
- Equation A has the solution \( h = 1 \)
- Equation B has the solution \( p = -\frac{149}{4} \)
- Equation C has the solution \( v = -\frac{81}{23} \)
Now evaluating the statements:
- Tamara says Equations A and C have the same solution. Incorrect.
- Payton says Equations B and C have the same solution. Incorrect.
- Krish says all three have the same solution. Incorrect.
- Haruki says that none of the equations have the same solution. Correct.
Therefore, the correct response is: Haruki.